SNR Analysis On L-Band Mobile Satellite System Under Building Effect - W. A. W. Z., Abidin; Saufi Affendy, Basri (UTM Press, 2015)
This paper presents the method to analyse the effect of building on the L-band Mobile Satellite (MS) system using low-power Global Positioning System (GPS) receiver. The method includes measurement, experimental and data analysis. The analysis of the signal performance under building effect measurement was carried out with respect to the signal to noise ratio (SNR), elevation and azimuth angle. In measurement method, the National Marine Electronics Association (NMEA) sentences obtained from the satellite via GPS receiver was used to get the signal propagation parameters. The NMEA Extractor used to extract the NMEA data using C++ programming language and Ngraph software to construct the graphical presentation for analysis method. The analysis shows relationship between SNR and elevation and azimuth angle. The comparison between open space and building effect was carried out and the results have shown that the presence of the building affect the quality of the satellite signal received.